Surgical management of advanced pachydermodactyly: a case report - Lee, Hyun Rok; Yoon, Yeongsik; Chung, Jae In (Archives of Hand and Microsurgery, 2025)
Pachydermodactyly is a rare, benign condition characterized by bilateral soft tissue thickening around the proximal interphalangeal joints in the fingers, often due to behaviors like finger cracking. Most cases are managed conservatively; however, surgical intervention may be necessary when conservative treatments fail. In this case, a 17-year-old male with 5-year persistent thickening on his right second finger underwent conservative treatment, which failed. Due to aesthetic concerns, he opted for surgical excision via bilateral mid-axial incision, preserving neurovascular structures. Histopathology showed increased collagen and fibrosis. Postoperative care included encouragement of finger mobilization and avoidance of cracking habits. After 1 year, the patient was satisfied with the appearance and function, with no recurrence. The case suggests surgical intervention can be effective when conservative methods are unsuccessful, especially for aesthetic or rapid functional improvement.